Functional characterizations and expression profiles of ADAR2 gene, responsible for RNA editing, in response to GCRV challenge in grass carp (Ctenopharyngodon idella). (September 2016) - Su, Juanjuan; Han, Baoquan; Rao, Youliang; Feng, Xiaoli; Su, Jianguo
Abstract: ADAR (adenosine deaminases acting on RNA)-mediated adenosine-to-inosine (A-to-I) editing to double-stranded RNA (dsRNA) is a critical arm of the antiviral response. The present study focused on the structural and functional characterizations of grass carp ( Ctenopharyngodon idella ) ADAR2 ( CiADAR2 ) gene. The complete genomic sequence of CiADAR2 is 150, 458 bp in length, containing 12 exons and 11 introns. The open reading frame (ORF) of 2100 bp encodes a polypeptide of 699 amino acids (aa) which contains three highly conservative domains — two N-terminal dsRNA binding domains (dsRBDs) and one C-terminal deaminase domain. The predicted crystal structure of CiADAR2 deaminase domain suggested a catalytic center form in the enzyme active site. CiADAR2 mRNA was ubiquitously expressed in the fifteen tested tissues, and was induced post GCRV challenge in spleen and head kidney and C. idella kidney (CIK) cells. The ex vivo expression of CiADAR2 protein was verified by the Flag (tag)-based western blot assay. Antiviral activity assay of CiADAR2 was manifested by the delayed appearance of cytopathic effect (CPE) and inhibition of GCRV yield at 48 h post infection. Furthermore, in CiADAR2 overexpression cells, mRNA expression levels of CiIFN1, CiTLR7 and CiTLR8 were facilitated at different time points after GCRV infection, comparing to those in control group. Taken together, it was indicated that ADAR2 was an antiviral cytokine against GCRV and anti-GCRV function mechanism might involve in the TLR7/8-regulated IFN-signaling. These findings suggested that CiADAR2 was a novel member engaging in antiviral innate immune defense in C. idella, which laid a foundation for the further mechanism research of ADAR2 in fishes. Highlights: ADAR2 gene, responsible for RNA editing, was characterized in grass carp. CiADAR2 mRNA expression profiles were investigated post GCRV challenge in vivo and in vitro . CiADAR2 protein overexpression in CIK cells inhibited GCRV proliferation. Anti-GCRV activity of CiADAR2 might involve in the TLR7/8-regulated IFN-signaling.